PMN Leukocytes and Fibroblasts Numbers on Wound Burn Healing on the Skin of White Rat after Administration of Ambonese Plantain Banana - Aryenti, Aryenti; Suryadi, Suryadi; Harijadi, Harijadi; Yuhernita, Yuhernita (UI Scholars Hub, 2012)
A study of ambonese plantain banana (Musa paradisiaca var sapientum Lamb) treatment in burn wound healing on the skin of white rats (Rattus novergicus) has been conducted. The wound healing of burn injuries was evaluated by counting the number of PMN leukocytes and fibroblasts at the 7th, 14th, and 21st days following the treatment. The study showed that the decrease in number of PMN leukocytes of subjects treated with ambonese plantain banana was relatively more significant compared to both negative and positive control (Bioplacenton ®). In contrast, an increasing number of fibroblasts was significantly demonstrated at the 14th and 21st days after treatment. In conclusion, ambonese plantain banana treatment in burn injuries will provide better results compared to both positive and negative controls.